2019
DOI: 10.1021/acscatal.9b00648
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Activity Descriptors for Iridium-Based Catalysts for the Electrochemical Oxygen Evolution Reaction (OER)

Abstract: Recent progress in the activity improvement of anode catalysts for acidic electrochemical water splitting is largely achieved through empirical studies of iridium-based bimetallic oxides. Practical, experimentally accessible, yet general predictors of catalytic OER activity have remained scarce. This study investigates iridium and iridium–nickel thin film model electrocatalysts for the OER and identifies a set of general ex situ properties that allow the reliable prediction of their OER activity. Well-defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 52 publications
3
93
0
Order By: Relevance
“…[ 132 ] The structure and composition of bimetallic oxides can be modulated by a variety of synthesis methods, including thermal decomposition and sputtering techniques. [ 133,134 ]…”
Section: Precious Metal‐based Oer Catalystsmentioning
confidence: 99%
“…[ 132 ] The structure and composition of bimetallic oxides can be modulated by a variety of synthesis methods, including thermal decomposition and sputtering techniques. [ 133,134 ]…”
Section: Precious Metal‐based Oer Catalystsmentioning
confidence: 99%
“…The identification and rigorous comparison of promising catalysts is essential for the rational design and development of more active and stable OER catalysts for PEM electrolysers. Due to an evident need to overcome this problem, recent studies have reported protocols and recommendations for the evaluation of the OER in acidic media, as well as Ir‐based catalysts for this reaction . Only few of them focus on the effect of the experimental parameters ( e. g .…”
Section: Figurementioning
confidence: 99%
“…[ 3 ] An amorphous form of electrochemically oxidized Ir (Ir III ) with the hydrated or hydroxylated structure has exhibited the highest catalytic activity among various material phases, owing to the flexible structure of catalytic sites. [ 4–6 ] Unfortunately, such Ir III oxides eventually worsen the OER performance because high potentials promote the oxidation and dissolution of active Ir during long‐term operation. [ 7–9 ] Meanwhile, Geiger et al showed that the rutile structure in IrO 2 (Ir IV ) exhibits much higher stability than amorphous Ir III oxides.…”
Section: Introductionmentioning
confidence: 99%